Facilities management in construction planning: Malaysian scenario - Yusuf, Sharif; Harun, Linariza; Osman, Omar (2008)

(untitled)
A good construction plan is the basis for developing the budget and the schedule for work. Developing the plan is a critical task in the management of construction and is generally concerned with completing a contract in the shortest possible time compatible with the budget. On the other hand facilities management provides project participants with good coordination, communication and encourages the employees to have personal responsibility in the design and planning process. The objectives of this paper is to explore the role of facilities management in construction planning, to examine the general perception of the local construction industry regarding facilities management principles and practices, and to study how facilities management supports the organizational development, management process and management of the resources, within the two knowledge areas defined by RIBA plan of work (pre-production and production). A questionnaire survey was conducted on those who are involved in construction planning, viz architects, engineers, quantity surveys and client/developers. One hundred fifty sets of questionnaires were posted to a selected sample of those professional in four areas: Kuala Lumpur (40), Selangor (40), Penang (35), Johor (35), 41 of them are replied; mean importance rating was analyzed on the data. The results of the survey showed that facilities management in the planning process gives all parties that are involved in the project the ability to measure their capability in order to complete the project on time, budget and quality, while keeping the customer and stakeholders satisfied. Proper planning at the outset makes it easy for design, workplace enhancement and renovation time of the project be carried out successfully, while reducing all costs, especially at the operational level. Hence, the general perception of facilities management in local the industry differs from person to person.